Compositional effects in Titan's thermospheric gravity waves. Issue 1 (16th January 2013) - Cui, J.; Lian, Y.; Müller‐Wodarg, I. C. F.
<x xml:space="preserve">Abstract</x> [1] In Titan's upper atmosphere, the density profiles of several constituents (N2, CH4, H2, and 29N2) as measured by the Cassini Ion Neutral Mass Spectrometer show periodical structures which we interpret as internal gravity waves. Compositional effects are frequently seen in the data, in which the wave structures in different constituents show different amplitudes and phase angles. We use a simple linearized wave perturbation theory to explain the observations, emphasizing their role as a useful diagnostic of the basic wave parameters. For the T39 flyby, the data‐model comparison constrains typical wavelength to be ~150–500 km, typical wave period from the Brunt‐Väisälä period of ~62 min up to ~6 h. Our calculations also illustrate that wave‐induced diffusion is important for CH4 and H2.